A survey of the genetics of stomach, liver, and adipose gene expression from a morbidly obese cohort - Greenawalt, Danielle M.; Dobrin, Radu; Chudin, Eugene; Hatoum, Ida J.; Suver, Christine; Beaulaurier, John; Zhang, Bin; Castro, Victor; Zhu, Jun; Sieberts, Solveig K.; Wang, Susanna; Molony, Cliona; et al. (Genome Research, 2011)
To map the genetics of gene expression in metabolically relevant tissues and investigate the diversity of expression SNPs (eSNPs) in multiple tissues from the same individual, we collected four tissues from approximately 1000 patients undergoing Roux-en-Y gastric bypass (RYGB) and clinical traits associated with their weight loss and co-morbidities. We then performed high-throughput genotyping and gene expression profiling and carried out a genome-wide association analyses for more than 100,000 gene expression traits representing four metabolically relevant tissues: liver, omental adipose, subcutaneous adipose, and stomach. We successfully identified 24,531 eSNPs corresponding to about 10,000 distinct genes. This represents the greatest number of eSNPs identified to our knowledge by any study to date and the first study to identify eSNPs from stomach tissue. We then demonstrate how these eSNPs provide a high-quality disease map for each tissue in morbidly obese patients to not only inform genetic associations identified in this cohort, but in previously published genome-wide association studies as well. These data can aid in elucidating the key networks associated with morbid obesity, response to RYGB, and disease as a whole.